Photosynthesis and growth of Kandelia candel (L.) Druce grown in different levels of external salinity - Phuong, Tran Thi; Tuan, Mai Sy (Academia Journal of Biology, 2015)
Photosynthesis and growth of Kandelia candel (L.) Druce grown in different levels of external salinity